Increasing the Use of Kidneys From Unconventional and High‐Risk Deceased Donors. Issue 11 (14th June 2016) - Heilman, R. L.; Mathur, A.; Smith, M. L.; Kaplan, B.; Reddy, K. S.
Abstract : In this paper, we have reviewed the literature and report on kidney donors that are currently used at relatively low rates. Kidneys from donors with acute kidney injury (AKI) seem to have outcomes equivalent to those from donors without AKI, provided one can rule out significant cortical necrosis. Kidneys from donors with preexisting diabetes or hypertension may have marginally lower aggregate survival but still provide patients with a significant benefit over remaining on the wait list. The Kidney Donor Profile Index derives only an aggregate association with survival with a very modest C statistic; therefore, the data indicated that this index should not be the sole reason to discard a kidney, except perhaps in patients with extremely low estimated posttransplant survival scores. It is important to note that the Scientific Registry of Transplant Recipients models of risk adjustment should allay concerns regarding regulatory issues for observed outcomes falling below expectations. The successful utilization of kidneys from donation after cardiac death over the past decade shows how expanding our thinking can translate into more patients benefiting from transplantation. Given the growing number of patients on the wait list, broadening our approach to kidney acceptance could have an important impact on the population with end‐stage renal disease. Many lives could be prolonged by carefully considering use of kidneys that are often discarded. Abstract : The authors summarize data from recent literature on clinical outcomes of increasing utilization of kidneys from unconventional and higher‐risk deceased donors.